STUDI EPIDEMIOLOGI PENYAKIT DEMAM BERDARAH DENGUE DI WILAYAH KERJA PUSKESMAS PURWOKERTO SELATAN KABUPATEN BANYUMAS TAHUN 2018 - Erna Lusianah; Budi Utomo (Buletin Keslingmas, 2019)
Dengue hemorrhagic disease (DHF) is an infectious disease transmitted by dengue virus and transmitted by Aedes Aegypti mosquitoes. Based on the report of Banyumas District Health Office, the number of Dengue Hemorrhagic Fever cases in Banyumas District in 2015 amounted to 264 cases, 2016 with 990 number, 2017 with 68 cases. the southern Purwokerto Kecamtan region from 2015 to 2017 with (IR = 2.20). The purpose of this research is to know the description of DHF incidence based on Epidemiology variable (person, time and place) in South Purwokerto Sub-district of Banyumas Regency 2015 until 2017. The type of research used is descriptive. Data collection is done by data search and interview. Data is presented in the form of narrative structures, graphs and tables. Data analysis is done by analysis of tables and graphs. The conclusions of the study were general patients between 16 - 55 years old with female gender and with the work of the Student. The time of the highest incidence of dengue cases was in January. The highest dispersion area is the Teluk district. And has been done dengue vector control periodically and continuously. The trick is to conduct PSN program and community counseling 1 week 1 times to maintain clean environment and do 3M plus activities to prevent the spread of DHF cases